The Effect of Different Warm-Up Protocols on the Motor and Technical Skills of Handball Players in Sports Education - Muhammed Zahit Kahraman; Tayfun İşlen; Ömer Faruk Bilici; Cengizhan Sari; Muhammed Fatih Bilici (Journal of Educational Issues, 2024)
Warm-up programs in sports education can provide positive developments in motor and technical skills. The objective of this study was to determine the acute effects of ballistic, dynamic, and static warm-up protocols on motor and technical skills in male handball players. Twelve male handball players (mean age: 19.50±3.97 years) from the second league in Turkey participated in this study voluntarily. Warm-up protocols were implemented for the participants at the same time on three different days. At the beginning of the study, the height and body masses of the handball players were measured. After each warm-up protocol, 9-m shot, over-the-block shot, vertical jump, T agility, 20-m sprint, flexibility, and flamingo balance tests were conducted on the participants. The normality level of the data was determined by the Shapiro-Wilk test using the SPSS statistical program. While Repeated Measures ANOVA and the Bonferroni test from post hoc analysis were applied to data with normal distribution, the Friedman test and the Wilcoxon signed-rank test with the Bonferroni correction were used for non-normally distributed data. According to our findings, there was a significant difference between the warm-up protocols in the T agility, flexibility, and over-the-block shooting tests (p < 0.05), while no significant difference was found in the vertical jump, 20-m sprint, balance, or 9-m shooting tests (p > 0.05). The ballistic warm-up protocol applied to male handball players in sports education provided positive improvements in flexibility and over-the-block shooting skills, while the dynamic warm-up protocol yielded positive improvements in agility and flexibility.